Provisions, Objectives and Reforms of Education Policies in Pakistan "An Analytical Review” - Aslam, Shumaila; Rizwan, Shafaq; Kiran, Dr. Zobia; Batool, Dr Tahira; Asghar, Muhammad Awais (ACADEMIA International Journal for Social Sciences, 2025)
This study presents a comprehensive review of Pakistan’s educational policies and their evolution since the country’s establishment in 1947. It focuses on analyzing the major objectives, reforms, and strategic directions set by successive governments in shaping the country’s educational landscape. The review covers the three main sectors of education in Pakistan: Primary, Secondary, and Higher Education, emphasizing their respective goals and developmental . The study provides a historical overview of educational policy development, tracing how various governments introduced policy measures to improve access, quality, and equity in education. Each policy initiative, from early post-independence efforts to more recent reforms, is examined in terms of its intended objectives, implementation strategies, and outcomes. Special attention is given to how the priorities in education policy have shifted over time in response to social, political, and economic changes in the country. Additionally, the report highlights the persistent challenges in both policy formulation and execution. Despite numerous efforts to modernize and expand the education system, Pakistan continues to face issues such as resource constraints, lack of effective implementation mechanisms, regional disparities, and gaps in educational quality. These challenges have often hindered the full realization of policy goals. Overall, the study aims to provide an insightful analysis of Pakistan’s educational policy evolution, illustrating both the progress achieved and the critical gaps that remain. By reviewing past initiatives, the document also offers a foundation for understanding future directions for educational development in Pakistan.